1998
DOI: 10.1177/073428299801600202
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation of the Multidimensional Students' Life Satisfaction Scale

Abstract: The psychometric properties of a children's life satisfaction measure (MSLSS; Huebner, 1994) were assessed with a middle school sample of 291 students. Similar to findings with elementary school students, the MSLSS demonstrated preliminary evidence of reliability and validity for research purposes. The results of confirmatory factor analyses supported the five satisfaction domains identified in previous research with younger students, along with a single higher-order general life satisfaction factor. Relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
162
2
16

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 250 publications
(197 citation statements)
references
References 38 publications
9
162
2
16
Order By: Relevance
“…However, the correlations between LS and the other personality dimensions measured remained largely unaltered after partialing out the effects of social desirability (Heaven 1989). Comparatively, a study by Huebner et al (1998) showed that the relationship between reports of LS and social desirability varied across the domains of the MSLSS, indicating the importance of social desirability as a determinant of LS (Gilman and Barry 2003;Huebner et al 1998); results which contradict the notion that a correlation between the total scores of LS and a social desirability measures reflects bias in measures of SWB (see McCrae and Costa 1983).…”
Section: Social Desirability Effectsmentioning
confidence: 44%
See 3 more Smart Citations
“…However, the correlations between LS and the other personality dimensions measured remained largely unaltered after partialing out the effects of social desirability (Heaven 1989). Comparatively, a study by Huebner et al (1998) showed that the relationship between reports of LS and social desirability varied across the domains of the MSLSS, indicating the importance of social desirability as a determinant of LS (Gilman and Barry 2003;Huebner et al 1998); results which contradict the notion that a correlation between the total scores of LS and a social desirability measures reflects bias in measures of SWB (see McCrae and Costa 1983).…”
Section: Social Desirability Effectsmentioning
confidence: 44%
“…Several studies, however, have noted specific relationships between demographic variables and youth LS. For example, Huebner et al (1998) found that age (M = 12.89) was weakly correlated with students' scores on the MSLSS domains. Ash and Huebner (2001) found that SES was positively related to LS (i.e.…”
Section: Demographics and Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…To measure life satisfaction, multiple measures were used, including the Satisfaction With Life scale (SWL; Diener et al, 1985) and the Self and Global subscales of the Multidimensional Life Satisfaction Scale (MSLSS; Huebner, 1994;Huebner, Laughlin, Ash, & Gilman, 1998). The SWL scale consists of five questions; total scores can range from 5 to 30, with higher scores indicating greater satisfaction with life.…”
Section: Methodsmentioning
confidence: 99%